Ecología reproductiva del Cormorán Imperial (Phalacrocorax atriceps), en Isla Deseada (Santa Cruz, Argentina) - Arrighi, Alejandro C. (1998)
We studied the breeding ecology of Imperial Shags (Phalacrocorax atriceps) in Deseada Island (Santa Cruz, Argentina), during the breeding season of 1994-95. The shags arrived to the island in early August, they re-builded their nests and started to lay eggs during late October, with a peak of egg production in the first two weeks of November. The modal clutch size was three eggs. Hatehing started in late November. The maximum mean brood size was observed in mid- Oecember (1.4 chicks). Hatehing success was 53%, whereas the survival of chicks was 60%. Nelther hatching success nor chick survival differed among nests located in distinct sectors of the colony. In mid- February the juvenile (approximately 60 days of age): adult ratio was 1:3. All the juvenile shags left the island in late March, together with most adults.